The greeting 'Rek' as an identity marker of "Komunitas Suroboyoan" on platform X - Hitakumala, Nur Azizah (Priviet Social Sciences Journal, 2025)
This study aims to examine how the greeting "rek" is used in the digital interactions of the Suroboyoan community on platform X and how this greeting marks and represents the identity of arek Suroboyo. Using a qualitative approach and communication ethnography methods, data was collected through tweet documentation and an online survey of 11 respondents. The analysis shows that "rek" is used in various forms, such as greetings, invitations, emotional expressions, and jokes, reflecting the informal and egalitarian communication style typical of Surabaya. The survey findings indicate that the majority of respondents consider "rek" a very distinctive greeting that is still relevant for use by the younger generation and functions as a marker of local identity. Through indexicality theory, "rek" is understood as a linguistic symbol that indexes social membership, cultural closeness, and a sense of community togetherness. Therefore, the greeting "rek" serves not only as a form of linguistic expression but also as a representation of social and cultural identity that is alive and developing in the digital communication practices of Surabaya's younger generation.